Traffic Modeling and Simulation on the Norra Promenaden- Packhusgatan Intersection, Sweden - Sara Wibawaning Respati (Jurnal Teknologi Terpadu, 2015)
Abstract  In this paper, the roundabout between Norra Promenaden and Packhusgatanin Norrkoping city, Sweden was studied and simulated. Afternoon rush hours (from 15:45 to 17:00) data such as the number of vehicles, travel time and queue lengths were observed. An AIMSUN model using those data was built to simulate the traffic at the roundabout intersection. This model was calibrated using travel times and queue lengths in each direction of the intersection and validated using travel time passing through the intersection. After obtaining a calibrated and validated simulation model of the real traffic, three improvements alternatives were introduced and analyzed. The first alternative is making two new free right turn ways, the second alternative is constructing an underpass from North to South direction and the third alternative is a bowtie intersection. The results show the decrease in travel time passing the intersection from all alternatives. However, each alternative has its own different impact on the local traffic and strengths/weaknesses which makes them favorable for different situations.  Keywords: Norrkoping, AIMSUN, roundabout, traffic simulation, traffic modeling       Abstrak                       Dalam penelitian ini, bundaran yang terletak pada jalan Norra Promenaden dan Packhusgatanin di kota Norrkoping, Swedia, diteliti dan disimulasikan. Data pada jam sibuk (15:45-17:00), yaitu data jumlah kendaraan, waktu tempuh dan panjang antrian diobservasi. Pemodelan dengan AIMSUN dibuat untuk mensimulasikan lalu lintas di bundaran. Model dikalibrasikan menggunakan data waktu tempuh dan panjang antrian untuk setiap lengan dan divalidasikan menggunakan data waktu tempuh melintasi bundaran. Setelah mendapatkan model yang baik, perbaikan simpang dengan tiga alternatif dilakukan dan dianalisis. Alternatif pertama adalah membuat sistem belok kanan langsung untuk dua lengan, kedua adalah membangun terowongan, dan ketiga adalah membuat bowtie intersection. Hasil simulasi menunjukkan penurunan waktu tempuh kendaraan melewati bundaran. Bagaimanapun setiap alternative memiliki dampak yang berbeda serta keunggulan dan kekurangan masing-masing yang membuat setiap alternatif tepat untuk keadaan yang berbeda. Kata Kunci : Norrkoping, AIMSUN, bundaran, simulasi lalu-lintas, pemodelan lalu-lintas